Change of the activated process of bituminous coal thermal decomposition depending on the method of applying the initiating inorganic salt additive; AIP Conference Proceedings; Vol. 2135 : Heat and mass transfer in the thermal control system of technical and technological energy equipment (HMTTSC 2019) - Larionov K. B. Kirill Borisovich (2019, 2019)
Title screen